Pengaruh Konsumsi Daging Wagyu dan Daging Meltique terhadap Kadar Kolesterol Mencit (Mus musculus) Jantan - Dwi Kurnia Wijaya; Katty Hendriana Priscillia Riwu; Iwan Doddy Dharmawibawa; Alifianita Anake Yansri; Candra Dwi Atma; Fitrah Ramdani; Muhammad Munawaroh; Muh. Sofyan (Biocaster : Jurnal Kajian Biologi, 2026)
Public demand for premium meat is rising, driving increased consumption of Wagyu and Meltique beef. This study aimed to determine the effect of consuming Wagyu and Meltique beef on cholesterol levels in male mice (Mus musculus). Male mice were selected due to their physiological, anatomical, nutritional, pathological, and metabolic similarities to humans, as well as their common use in cholesterol research. A total of 25 male mice were used in this study, which was conducted from March to April 2026 at the Veterinary Medicine Laboratory (RSHP) of Mandalika University of Education (UNDIKMA). Cholesterol levels were assessed by collecting blood from the tail vein of treated mice on days 7, 14, 21, and 28 using heparinized capillary tubes. Cholesterol levels were measured periodically and analyzed using a one-way ANOVA test. The results indicated that the consumption of both Wagyu and Meltique beef was associated with increased cholesterol levels in male mice. In the Wagyu group, levels rose from 81.22 mg/dL in the first week to 102.00 mg/dL in the fourth week, while the Meltique group saw an increase from 98.33 mg/dL to 123.22 mg/dL over the same period. The study concluded that the consumption of Wagyu and Meltique beef had a significant effect on increasing cholesterol levels in male mice (Mus musculus).